Erratum in “Volumetry versus linear diameter lung nodule measurement: an ultra-low-dose computed tomography lung cancer screening study” (doi: 10.17816/DD117481) - Maria M. Suchilova; Ivan A. Blokhin; Olga O. Aleshina; Victor A. Gombolevskiy; Roman V. Reshetnikov; Viktor Yu. Bosin; Olga V. Omelyanskaya (Digital Diagnostics, 2023)
In the article "Volumetry versus linear diameter lung nodule measurement: an ultra-low-dose computed tomography lung cancer screening study" published in Digital Diagnostics journal Volume 4 Issue 1 in 2023 (doi: 10.17816/DD117481) contained an error in the paragraph with data of funding sources for the study.